USE OF VIBRATION SENSOR AS DETECTION OF RAILWAY IN MECHANICAL SIGNALING SYSTEMS - S.T. M.T., Sukenda; Maulana S, Wawan; L, Septiane; M., Irvan Y; N. S, Lukman (International Journal of Psychosocial Rehabilitation, 2020)
Interlocking equipment used to secure a system. One of the systems on mechanical signaling that is contained in trains. Mechanical signaling is used to form, lock, and control so that the system is safe from errors that occur in the system. In the world of railroad signaling mechanically it is very much needed so that the train route remains on the correct and safe lane. The railroad to be traversed by the train is carried out mechanically. The development of electronic technology can have an impact on railroad signaling. So that the application of electronic technology can be done on railroad signaling in Indonesia. Rail contact, mechanical signaling that is used to detect the presence of trains. Equipment, rail contacts, to detect the presence of facilities on the railway line at the emplacement. The way rail contacts work uses an iron lever that is in direct contact with the rail wheels so that the movement of the lever causes the switch in the device to be active. Levers that are often stepped on by the train’s wheels cause wear. A worn lever causes the level of precision to weaken, making it unsafe for trains to be on the right track. The application of electronic technology, a microcontroller, can replace the worn lever. The SW-420 sensor as a vibration detector is integrated with a microcontroller to determine the presence of a train. This sensor can be applied as a train detector by utilizing vibrations on the rails. From the results of trials conducted, the system with sensors that are built can detect rail vibrations when the railroad stepped on the rail. So that train movement can be detected, and the microcontroller can show the vibration value data in real time.